HEALTH BELIEF MODEL APPROACH TO MOSQUITO NEST ERADICATION BEHAVIOUR (PSN) IN DHF INCIDENCE IN CIPAMOKOLAN HEALTH CENTRE ENVIRONMENT - Lolan, Yosef Pandai; Sinaga, Yakobus Lau De Yung; Somantri, Ucu Wandi (HEARTY, 2025)
Indonesia until July 2020 reached 17,700 cases. There are 10 provinces that reported the highest number of cases, namely in West Java 10,772 cases, Bali 8,930 cases, East Java 5,948 cases, NTT 5,539 cases, Lampung 5,135 cases, DKI Jakarta 4,227 cases, NTB 3,796 cases, Central Java 2,846 cases, Yogyakarta 2,720 cases, and Riau 2,255 cases. Meanwhile, in 2019 the number of cases was very high at 112,954. In addition, the number of deaths throughout Indonesia reached 459. However, the number of cases and number of deaths in 2020 is still low when compared to 2019. In 2019 the incidence of Dengue Fever (DHF) in West Java was high at 23,296 people, with 145 deaths. In 2019 the incidence of Dengue Fever (DHF) was still a problem in Bandung City, it could potentially cause an Extraordinary Event (KLB). This study aims to determine the relationship between the Health Belief Model (Vulnerability, Frailty, Cues to Action, Benefits and Barriers) with Mosquito Nest Eradication Behaviour. This research was conducted with quantitative research using Cross Sectional, the sampling technique used was Stratified random sampling technique. In the results of this study, one variable was found to be related, namely the benefit variable with the results of chi square analysis obtained a p value of 0.000 (P value ≥ 0.05). The conclusion of this study is that most people in the cipamokolan puskesmas environment have vulnerable, severe, perform actions, are not useful and are hampered by PSN behaviour.